The Challenge of Implementing Sharia Principles in Zakat Digitalization: Between System Efficiency and Compliance with Islamic Law - Kiki Reskia Amalia DT; Supriadi; Kamaruddin (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2025)
This article aims to describe the challenges of applying sharia principles in the digitalization of zakat; between system efficiency and adherence to Islamic law. This research uses a descriptive qualitative method, with a literature-based approach. Various works related to this research were collected from various literature sources, including scientific journals, online articles, books, documents, and others. The result of this research is that the digitalization of zakat provides a great opportunity to improve the effectiveness, transparency, and ease of access to the zakat system, but it also has various challenges, which include regulatory vagueness, high sharia compliance demands, data security and consumer protection, lack of digital Islamic financial literacy, and digital infrastructure inequality. Therefore, cooperation is needed from various parties, including the government, financial institutions, religious authorities, and the community, by making maqashid sharia as the main foundation. So that the digitalization of zakat is not only legal under Islamic law but also beneficial for the general public, and also still adheres to sharia principles.